2023
DOI: 10.3390/ijms24119714
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulant Properties of Protein Hydrolysates: Recent Advances and Future Challenges

Abstract: Over the past decade, plant biostimulants have been increasingly used in agriculture as environment-friendly tools that improve the sustainability and resilience of crop production systems under environmental stresses. Protein hydrolysates (PHs) are a main category of biostimulants produced by chemical or enzymatic hydrolysis of proteins from animal or plant sources. Mostly composed of amino acids and peptides, PHs have a beneficial effect on multiple physiological processes, including photosynthetic activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 174 publications
0
12
0
Order By: Relevance
“…On the other hand, PH promoted an accumulation of primary metabolites inducing a great support of photosynthesis and plant use of energy for plant growth over a longer period of the plant cycle resulting in a longer fruit production and higher yield. Several studies showed that the application of PH can boost crop yields and performance by activating carbon primary metabolism and N assimilation ( Colla et al., 2017 ; Rouphael et al., 2018 ; Malécange et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PH promoted an accumulation of primary metabolites inducing a great support of photosynthesis and plant use of energy for plant growth over a longer period of the plant cycle resulting in a longer fruit production and higher yield. Several studies showed that the application of PH can boost crop yields and performance by activating carbon primary metabolism and N assimilation ( Colla et al., 2017 ; Rouphael et al., 2018 ; Malécange et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…It can also positively influence the leaf area and yield of horticultural plants and fruit trees [ 165 , 166 ]. The exogenous utilization of protein hydrolysate and isolated amino acids can promote plant antioxidant performance by improving the non-enzymatic and enzymatic antioxidant defense machinery of the cell [ 167 ]. The most important effects of different kinds of protein hydrolysates have been shown in Table 3 .…”
Section: Protein Hydrolysatesmentioning
confidence: 99%
“…Overall, most studies reported that protein hydrolysates have the quality of improving plant endurance, mainly by enhancing antioxidant activity in the plant tissues, under the action of unfavorable environmental conditions [5,46].…”
Section: Influence Of the Treatment On The Antioxidant Activity Of Th...mentioning
confidence: 99%
“…Containing amino acids and peptides, protein hydrolysates have an especially positive influence on several physiological processes, including photosynthetic activity, nutrient assimilation, and translocation in plants, and also accumulation of bioactive compounds [5]. Regarding the action mechanism of protein hydrolysates in plants, recent studies indicate that they are directly involved in stimulating carbon and nitrogen metabolism, interfering with hormonal activity.…”
Section: Introductionmentioning
confidence: 99%